Implementation of STEAM project-based learning in developing early childhood cooperation - Rokyal Harjanty; Fithrii Muzdalifah (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
The 2013 curriculum for early childhood education with an integrative thematic and scientific approach is very suitable for integrating STEAM-based learning as it is carried out through various contexts to bring subject matter closer to everyday life or the themes are close to the world of children. However, children's social skills have not developed well; children have not been able to cooperate with their peers. The aim of this research was to develop early childhood cooperation by implementing STEAM project-based learning (PjBL). This study used classroom action research and it involved 15 children with an age range of 5-6 years in Salsabil Early Childhood Education, Telagawaru, West Nusa Tenggara. Data were obtained through observation regarding the activities of the teachers and children. The result showed that the cooperation among children improved significantly in cycle 1 to 3 after implementing STEAM PjBL. Therefore, the implication of STEAM PJBL can develop the ability to work together in early childhood.